Endotracheal Tube Placement Confirmation with Bedside Ultrasonography in the Pediatric Intensive Care Unit: A Validation Study - Chandnani, Harsha K.; Maxson, Ivanna N.; Mittal, Disha K.; Dehom, Salem; Moretti, Anthony; Dinh, Vi A.; Lopez, Merrick; Ejike, Janeth C. (Journal of Pediatric Intensive Care, 2020)
Critically ill patients who are intubated undergo multiple chest X-rays (CXRs) to determine endotracheal tube position; however, other modalities can save time, medical expenses, and radiation exposure. In this article, we evaluated the validity and interrater reliability of ultrasound to confirm endotracheal tube (ETT) position in patients. A prospective study was performed on intubated patients with cuffed ETTs. The accuracy of ultrasound to confirm correct ETT placement in 92 patients was 97.8%. Sensitivity, positive predictive value, and agreement of 97.7, 93.3, and 91.3% were found on comparing ultrasound to CXR findings. Ultrasound is feasible, reliable, and has good interrater reliability in assessing correct ETT position in children.
Keywords: ultrasound; endotracheal intubation; radiation